Legal Protection for Female Victims of Rape with Disabilities (A Study of Court Decision Number: 250/Pid.Sus/2023/Pn Pbm) - Samuel Simangunsong; Chairuni Nasution; Ismaidar Ismaidar (Journal of Research in Social Science and Humanities, 2025)
Women with disabilities are part of vulnerable groups who also play an important role in sustainable development. In Indonesia, the protection of women and persons with disabilities is a crucial aspect of guaranteeing human rights; however, various forms of violence and discrimination continue to occur, including rape against women with disabilities. This study formulates two main issues, namely: (1) how the implementation of Law of the Republic of Indonesia Number 8 of 2016 on Persons with Disabilities functions as formal criminal law in Indonesia, and (2) how legal protection is provided to female victims of rape with disabilities based on the study of Court Decision Number 250/Pid.Sus/2023/PN Pbm. This research employs a normative legal approach with a case study type. Data were collected through library research on statutory regulations, court decisions, legal literature, and reports from official institutions. The analysis was conducted descriptively, juridically-normatively, and critically, with an additional juridical-sociological approach to assess the implementation of the law in judicial practice. Data sources include court decision texts, relevant laws and regulations, legal literature, journals, and supporting documents. The findings indicate that the implementation of Law of the Republic of Indonesia Number 8 of 2016 in formal criminal law remains partial, although it has begun to move toward an inclusive justice system. Law enforcement officers are obliged to provide reasonable accommodation for persons with disabilities, including interpreters, psychologists, and legal companions. The case study of Decision Number 250/Pid.Sus/2023/PN Pbm demonstrates adequate repressive legal protection, reflected in the aggravation of punishment for the perpetrator and empathetic treatment of the victim; however, rehabilitative and preventive dimensions still need to be strengthened. In conclusion, Law of the Republic of Indonesia Number 8 of 2016 provides a legal basis for the protection of women with disabilities, yet its implementation remains inconsistent. Strengthening inter-agency coordination and improving the capacity of law enforcement officers are necessary to ensure comprehensive, fair, and equitable legal protection in accordance with the Constitution and international human rights standards